mRNA biogenesis-related helicase eIF4AIII from Arabidopsis thaliana is an important factor for abiotic stress adaptation - Pascuan, Cecilia Gabriela; Frare, Romina Alejandra; Alleva, Karina Edith; Ayub, Nicolás Daniel; Soto, Gabriela Cinthia (2017)
Similar to other plant species, Arabidopsis has a huge repertoire of predicted helicases, including the eIF4AIII factor, a putative component of the exon junction complex related to mRNA biogenesis. In this article, we integrated evolutionary and functional approaches to have a better understanding of eIF4AIII function in plants. Phylogenetic analysis showed that the mRNA biogenesisrelated helicase eIF4AIII is the ortholog of the stress-related helicases PDH45 from Pisum sativum and MH1 from Medicago sativa, suggesting evolutionary and probably functional equivalences between mRNA biogenesis and stress-related plant helicases. Molecular and genetic analyses confirmed the relevance of eIF4AIII during abiotic stress adaptation in Arabidopsis. Therefore, in addition to its function in mRNA biogenesis, eIF4AIII can play a role in abiotic stress adaptation.